Różne oblicza sławy. Młodzi celebryci o popularności = Different faces of fame. Young celebrities about popularity - Piotrowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author attempts to analyze the value of "fame". This article showed the attitude of selected young celebrities to fame. The goal of the article was to establish the motivation that drives young people to fame and to determine whether fame was for them a value in itself or if it was treated instrumentally.
Keywords: celebryci; popularność; sława; socjalizacja do sławy; celebrity; popularity; fame; socialization to fame